2016
DOI: 10.3390/ijms17010120
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Rich Plasma Increases the Levels of Catabolic Molecules and Cellular Dedifferentiation in the Meniscus of a Rabbit Model

Abstract: Despite the susceptibility to frequent intrinsic and extrinsic injuries, especially in the inner zone, the meniscus does not heal spontaneously owing to its poor vascularity. In this study, the effect of platelet-rich plasma (PRP), containing various growth factors, on meniscal mechanisms was examined under normal and post-traumatic inflammatory conditions. Isolated primary meniscal cells of New Zealand white (NZW) rabbits were incubated for 3, 10, 14 and 21 days with PRP(−), 10% PRP (PRP(+)), IL(+) or IL(+)PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 56 publications
2
21
0
Order By: Relevance
“…A review of the literature on the chondrogenic effects of PRP in vitro, shows mixed results. Like our study, Lee et al, showed that 10% PRP increased the fibrous Col1a1 phenotype and decreased Col2a1 gene expression in meniscal cartilage from healthy young rabbits. In contrast, a study by Jeyakumar et al, showed that compared to 10% fetal calf serum, 10% PRP from healthy donors increased Col2a1 and decreased Col1a1 mRNA in human OA chondrocytes.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…A review of the literature on the chondrogenic effects of PRP in vitro, shows mixed results. Like our study, Lee et al, showed that 10% PRP increased the fibrous Col1a1 phenotype and decreased Col2a1 gene expression in meniscal cartilage from healthy young rabbits. In contrast, a study by Jeyakumar et al, showed that compared to 10% fetal calf serum, 10% PRP from healthy donors increased Col2a1 and decreased Col1a1 mRNA in human OA chondrocytes.…”
Section: Discussionsupporting
confidence: 83%
“…The increase in MMPs were significantly greater with H‐PRP and were not affected by the GF or inflammatory mediator grouping. Other studies have also shown that PRP upregulates MMPs, with the hypothesis being that the concentrated inflammatory cytokines (IL‐1β and TNF‐α) within PRP activates the known MMP pathways to stimulate remodeling . Research with APS made from PRP with increased concentrations of anti‐inflammatory proteins have been shown to reduce MMP‐13 production from chondrocytes stimulated with IL‐1β and TNF‐α .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is believed that mesenchymal stem cells are necessary for repair of meniscus lesions in the avascular zone [ 12 ]. Additionally, in a recent article by Lee et al on a rabbit model of circular defect, PRP treatment failed to help in the production of meniscus cartilage, and it instead accelerated fibrosis and increased the production of catabolic molecules [ 48 ]. This might be a very important finding, as human studies have shown that catabolic activity in meniscus tissue may help identify patients who are at risk for progression of osteoarthritis following partial meniscectomy [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is collected from peripheral veins and contains several growth factors such as vascular endothelial growth factor (VEGF), epidermal growth factor (EGF), platelet derived growth factor (PDGF), transforming growth factor (TGF) and other cytokines that stimulate proliferation and growth. Recently, PRP has been used in several medical conditions in ophthalmology, orthopedics, surgery and wound healing but it's efficacy in endometrial growth has not been fully elucidated [6,7,8,9,10,11,12] .…”
Section: Original Introductionmentioning
confidence: 99%